Syphilis testing and treatment outcomes among people experiencing homelessness: a street medicine intervention in South Los Angeles, California - Kim, Josephine Yoolie; Sukhija-Cohen, Adam Carl; Samidon, Suhail Abdeen; Robinson, Manda Beth; Ordenana, Maria Jose; McGrath, Mark Roy (Sexually transmitted infections, 2025)
To evaluate the outcomes of a street medicine intervention offering syphilis testing and treatment to people experiencing homelessness in South Los Angeles, California-a population disproportionately affected by syphilis and underserved by traditional healthcare systems. From September 2024 to January 2025, a multidisciplinary street medicine team provided testing and treatment for syphilis during outreach visits to patients experiencing homelessness. A total of 99 patients were tested using the reverse syphilis testing algorithm. Demographic data included gender, race/ethnicity, substance use disorder, mental illness and HIV status. χ tests were used to evaluate associations between syphilis diagnosis and each demographic characteristic. Thirty-six (36.4%) of the 99 patients had reactive syphilis test results, with 94.4% (n=34) classified as late-stage infections. Of those diagnosed, 72.2% (n=26) were treated during follow-up visits. Statistically significant associations were found between syphilis diagnosis and gender (p=0.002), substance use disorder (p=0.008) and HIV status (p=0.020). Patients identifying as female or transgender female, and those with cooccurring substance use disorder or HIV, were more likely to be diagnosed with syphilis. This study demonstrates the feasibility and outcomes of delivering sexually transmitted infection care through street medicine. The high prevalence of late-stage syphilis and its syndemic overlap with substance use disorder and HIV underscores the need for low-barrier, community-based services. Street medicine interventions should be recognised and resourced as essential tools in public health responses to rising syphilis rates, particularly among unhoused populations.